Si loin, si proche : distance sociale et proximité physique dans le travail domestique rémunéré au Brésil pendant la pandémie de Covid-19 - Ana Julieta Teodoro Cleaver (GéoProximitéS, 2024)
Paid domestic work is a social fact strongly defined by racial, class, gender, and territory relations, which reflect social hierarchies and differentiation within Brazilian society. The social relevance of paid domestic workers in Brazil, a country with a large gap in access to socio-reproductive public services, is invertedly proportional to their social acknowledgment, income, and social protection. At the bottom of the Brazilian social pyramid, paid domestic workers are particularly vulnerable during socioeconomic crises. The covid 19 pandemic and an economic crisis in Brazil increased social inequalities, without effective public action to reduce its consequences. Informed by secondary sources and by public statistics analysis, this article is drawn on the contradiction between the physical proximity and the social distance that is inherent to paid domestic work aiming to present the main challenges that paid domestic workers experienced during the most critical period of the sanitary crisis.